Comparison of microwave and furnace melting for glasses to immobilise Fe-corrosion products. Issue 6 (2nd November 2019) - Mishra, H.; Ananthanarayanan, A.; Rao, R.; Shah, J. G.; Manohar, S.; Tiwari, A. P.
ABSTRACT: This study reports a comparison between Fe-based corrosion products immobilised by direct vitrification through furnace melting versus microwave melting. Although microwave melting is faster, the Fe-corrosion product does not dissolve in the melt and is encapsulated by the vitreous phase. In comparison, for furnace melting, complete dissolution of the corrosion product in the glass is obtained till the solubility limits are exceeded. In both cases, Fe release is low indicating that either strategy may be employed for immobilisation depending upon the species captured in the Fe-corrosion product.